EUROPEAN INTEROPERABILITY FRAMEWORK & E-CODEX: An Assessment of both European Initiatives towards Interoperability - Konishi de Souza, Eduardo (My University, 2012)
Due to the necessity of achieving greater interoperability among the European Union (EU) Member States’ public services, the European Interoperability Framework (EIF) was created. This framework provides guidelines to projects towards cross-border interoperability of EU Member States. One of such projects is the e-CODEX. The purpose of this thesis is, therefore, to assess how useful the EIF is, how e-CODEX stands in compliance to the EIF and ultimately answer whether the e-CODEX should fulfill its intended purpose or not. To answer these questions, I divided the research in two distinct sections: the first one compares the EIF against the American initiative towards interoperability, the Federal Enterprise Architecture (FEA); and the second one assesses to what extent the e-CODEX follows the EIF and to what extent the EIF covers e-CODEX’s needs in the form of a questionnaire sent to experts in e-CODEX’s Member States. By the conclusion, I summarize the findings in each section, derive some new findings by combining the previous ones, and finally suggest some recommendations and a topic for future research.